Faktor Yang Mempengaruhi Kepuasan Pembelajaran Mahasiswa Selama Masa Pandemi Covid-19 Pada Mahasiswa Jurusan Akuntansi Di Universitas Kristen Petra - Olivia Yuriko Sudarjo; Sany Sany (Business Accounting Review, 2021)
The purpose of this research is to find the effect of internet facility, platform, learner-learner interaction and learner-instructor interaction on student satisfaction. This research uses a quantitative method by distributing questionnaires through Google Form and using a Likert scale. The research sample consisted of 179 students from the Departement of Business Accounting, Tax Accounting and International Business Accounting (class of 2017-2021). This research was processed using SPSS software by testing the validity, reliability, t test and coefficient of determination test. The results of this research are internet facilities and learner-instructor interaction have a significant positive effect on student satisfaction during online learning, while the platform and learner-learner interaction have an insignificant positive effect on student satisfaction during online learning.